Simulation Analysis of the Tensile Mechanical Properties of a Hydraulic Strain Clamp-Conductor System - Zhongfei Ye; Kai Pang; Yuanxiang Du; Guifeng Zhao; Shao Huang; Meng Zhang (Advances in Materials Science and Engineering)
Herein, a three-dimensional (3D) finite element model of a strain clamp-conductor system is established, with an NY-300/40 compression-type strain clamp taken as an example. The tensile load-carrying capacity of the strain clamp under standard crimping conditions is analyzed with LS-DYNA software, and the simulation results are compared with the experimental results to verify the accuracy of the model. On this basis, the tensile load-bearing capacity and failure mode of the strain clamp-conductor system are analyzed when the crimping length between the steel anchor and steel core is insufficient. Studies have shown that the grip strength of a strain clamp is provided mainly by the crimping between the steel anchor and the steel core. Under standard crimping conditions, the tensile load-bearing capacity of the strain clamp can meet the design requirements. Moreover, because the crimping length between the steel anchor and steel core is sufficient, the strain clamp fails due to aluminum strand breakage rather than the steel core being pulled out of the steel anchor. When the crimping length is insufficient, the grip strength of the strain clamp decreases with decreasing crimping length. Although the absolute value of the grip strength does not decrease significantly, the failure mode gradually changes from the breakage of the aluminum strands to the steel core being pulled out of the steel anchor. For the NY-300/40 compression-type strain clamp, the corresponding critical crimping length (i.e., when the change in failure modes occurs) between the steel core and the steel anchor is 50∼60 mm.